Adoption of Integrated Micro Banking Systems in Microfinance Institutions: An Analysis Using the Theory Acceptance Model - Eti Kusmiati; Lita Wulantika; Irfan Rizki Gumilar; Eka Yuliana; Prima Satriya Januarta (Australasian Accounting, Business and Finance Journal, 2024)
This study examines the adoption of Integrated Micro Banking System technology using the Theory Acceptance Model in PT Lembaga Keuangan Mikro (MFI). Employing quantitative research methods with descriptive and associative approaches, the study focused on users of the Integrated Micro Banking System at PT LKM Garut Regency. A total of 83 individuals were sampled using a census sampling technique. Data was analysed using the Structural Equation Method – Partial Least Square (SEM-PLS). The findings showed that all six hypotheses developed supported the researchers' initial guesses. Perceived Usefulness, Perceived Ease of Use, Perceived Trust, and Attitude, directly or indirectly, can explain and predict users' adoption of Integrated Micro Banking System technology. Therefore, these results serve as a valuable reference, especially for the management team of Microfinance Institutions in adopting technology and formulating relevant policies.
Keywords: Microfinance Institutions; Theory Acceptance Model; Integrated Micro Banking System